1992
DOI: 10.1046/j.1537-2995.1992.32192116435.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss and replacement in total hip arthroplasty: a multicenter study. The Preoperative Autologous Blood Donation Study Group

Abstract: To determine blood loss, the number of transfusions, and the hemoglobin levels achieved in patients via transfusion in the course of total hip arthroplasty, 324 patient records from 1987 through 1989 were reviewed at three university and three community hospitals. Calculated blood loss was 3.2 +/- 1.3 units in primary procedures and 4.0 +/- 2.1 units in revision procedures (mean +/- SD). Of 777 red cell units transfused, 455 (59%) were autologous units. Transfused patients received 2.0 +/- 1.8 units for primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 16 publications
2
40
0
1
Order By: Relevance
“…21%) since the introduction of more standardised guidelines. [25][26][27] There was no incidence of haematoma formation in our study, and only one patient required a transfusion of 2 units RCC, which is comparable to both the mean population according to Toy and the peri-operative transfusion volume of 2.8 units RCC according to Yoo et al 19,23 The comparable transfusion requirements may be because the patients with haemophilia tend to be younger overall and may tolerate a higher blood loss without the need for transfusion. The mean age in our study was 56 years, and 36 years in the patient group from Yoo et al 22 Haemoglobin drops have been suggested to be a better estimate of overall blood loss than intra-operative assessment, but in a large study of 198 orthopaedic patients undergoing major surgery, Howe et al demonstrated that clinical estimation of blood loss correlated well with actual change in peri-operative haemoglobin.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…21%) since the introduction of more standardised guidelines. [25][26][27] There was no incidence of haematoma formation in our study, and only one patient required a transfusion of 2 units RCC, which is comparable to both the mean population according to Toy and the peri-operative transfusion volume of 2.8 units RCC according to Yoo et al 19,23 The comparable transfusion requirements may be because the patients with haemophilia tend to be younger overall and may tolerate a higher blood loss without the need for transfusion. The mean age in our study was 56 years, and 36 years in the patient group from Yoo et al 22 Haemoglobin drops have been suggested to be a better estimate of overall blood loss than intra-operative assessment, but in a large study of 198 orthopaedic patients undergoing major surgery, Howe et al demonstrated that clinical estimation of blood loss correlated well with actual change in peri-operative haemoglobin.…”
Section: Discussionsupporting
confidence: 72%
“…13 In a large multi-centre study, Toy et al estimated the mean blood loss for 324 primary THA to be in the order of 3.2 AE 1.3 units RCC, and the mean volume transfused if required was 2 units RCC. 23 Various factors such as type of anaesthesia, operative approach, procedure duration and implant type can have an influence the total amount. Even when all influencing factors are equal, blood loss is still variable.…”
Section: Discussionmentioning
confidence: 99%
“…in primary THR, the blood loss is 3.2+/--1.3 units while in revision THR it goes up to 4.0+/--2.1 units. In primary TKR , the blood loss ranges from 1000 to 1500ml (8).During bilateral TKR, blood loss may be greater for the second knee and alterations in coagulation have been noted [8][9][10][11] . The purpose of reducing the peri-operative blood loss protocol is to decrease the need of allogenic blood transfusion thus eliminating transfusion related complications.…”
Section: Name and Address Of Corresponding Authormentioning
confidence: 99%
“…Studies have shown that donation of autologous blood is the biggest predictor of a transfusion after total joint replacement. 9,10 Studies have also shown that hemoglobin concentrations prior to surgery were inversely related to the need for allogeneic transfusion. 11,12 In total joint replacement surgery, a significant amount of donated autologous blood is discarded and wasted after the procedure is performed, resulting in a huge unnecessary cost to society.…”
Section: Preoperative Autologous Blood Donationmentioning
confidence: 99%